Phytogeographical Analysis of the Flora of North-central Uttar Pradesh, India - Misra, V. K.; Sharma, S. C. (Indian Forester, 2010)
The phytogeographical analysis of the flora of north-central Uttar Pradesh was made during its floristic survey (2004-2009). A total of 944 angiospermic species belonging to 510 genera and 130 families are reported from the study area and these are classified into 13 floristic elements viz. Pantropical (27.12%), Indian (19.6%), Indo-Malayan (17.27%), Neotropical (9.32%), Tropical Indo-African (8.37%), Cosmopolitan (6.04%), Temperate (4.03%), Eurasian (3.28%), Mediterranean (2.54%), Indo-Chinese (0.85%), Austro-Asian (0.64%), Sudano-Rajasthanian (0.64%) and Saharo-Sindian (0.32%). The dominance of pantropical elements in the study area may be due to the adaptation of entrant species to the typical tropical climatic conditions prevailing during major part of the year. The phytogeographical richness of the study area may be due to its unique geographical location where different climatic zones are appearing to be merged with one another.